YouTube educational videos for peripheral block learning and application: A survey of Turkish anesthesiologists; how successful - Alver, Selçuk; Çiftçi, Bahadır; Gölboyu, Birzat Emre; Sargolzaeimoghaddam, Mohammad; Erdoğan, Cem; Alıcı, Hacı Ahmet; Ahıskalıoğlu, Ali (AVES, 2023)
Objective: The aims of this survey study were to evaluate the contribution of YouTube to nerve-block learn-ing/education and the advantages and disadvantages of the YouTube. Materials and Methods: A total of 24 questions were selected for the survey by consensus of the authors. Information in the form of web data was obtained through an electronic data form that was distributed via WhatsApp to known email addresses and phone numbers of 300 practitioners (anesthesia residents, anes-thesiologists, and academicians). There were a total of 24 questions on the survey. The first section included 5 questions collecting demographic data, and the second part encompassed 19 questions about the YouTube nerve block videos. Results: Among the participants, 232 of practitioners (86.9%) performed peripheral nerve blocks, and only 35 practitioners (13.1%) had no experience of nerve blocks so and used YouTube videos for educational purposes. According to our results, YouTube videos frequently improved performance. In addition, YouTube improved the training of practitioners in terms of the type of block procedure, identifying anatomical land-marks, target structures like nerves and blood vessels, needle visualization, needle depth, and patient position. Conclusion: YouTube contributes to the performance of regional anesthesia and to learning at all academic levels. It should not be forgotten that such videos are not peer reviewed by professionals in the relevant field.
Keywords: Nerve Block; Regional Anesthesia; Survey; Ultrasound; YouTube